Comparison of Risk Assessment Models for Predicting Postpartum Venous Thromboembolism - Yonghui Xu; Sha Zhu; Ji He; XingSheng Xue; Fei Xiao (Clinical and Experimental Obstetrics & Gynecology)
Background: Venous thromboembolism (VTE) remains a leading cause of sudden death in obstetric patients. Despite advancements in diagnostic and therapeutic approaches, the incidence of VTE continues to rise. This study aimed to validate the accuracy of currently used risk assessment models (RAMs) for predicting postpartum VTE. Methods: This retrospective study was conducted from February 2019 to February 2024. The Chinese Expert Consensus on the Prevention and Treatment of VTE during Pregnancy and Puerperium (Chinese Consensus), and the Queensland Clinical Guideline (QLD guideline) were used to evaluate VTE risk. Risk factors were compared between the VTE group and the control groups. The predictive performance of the two RAMs was assessed by analyzing the area under the curve (AUC) of the receiver operating characteristic (ROC). Results: A total of 560 postpartum women were included, comprising 140 cases with VTE and 420 cases without VTE (controls). Significant differences between the two groups were observed for D-dimer levels, platelet (PLT) count, length of hospital stay, gestational age, body mass index (BMI) ≥25 kg/m2, postpartum hemorrhage (PPH), premature birth, and delivery mode (all p < 0.05). A higher proportion of anti-phospholipid antibody positivity was found in the VTE group (p = 0.054), while assisted reproductive technology (ART), emergency cesarean delivery, and elevated total cholesterol levels were more frequent in the control group (p < 0.05). Cesarean delivery was the most frequent risk factor triggering VTE, followed by age ≥35 years, and ART. However, stillbirth (n = 2, 66.7%), anti-phospholipid antibody positivity (n = 9, 52.9%), and PPH (n = 13, 52%) demonstrated the highest proportions of VTE. Notably, VTE occurred in the low-risk group, with an incidence of 20.6% according to the QLD guideline and 24.6% according to the Chinese Consensus. 2 VTE cases were observed in patients with a score of 0. The QLD guideline exhibited higher sensitivity than the Chinese Consensus (0.81 vs. 0.69), but lower specificity (0.64 vs. 0.83). The AUCs for predicting postpartum VTE were 0.624 (p < 0.001) for the QLD guideline and 0.538 (p > 0.05) for the Chinese Consensus. Conclusions: PPH, anti-phospholipid antibody positivity, and D-dimer levels were closely associated with thrombosis. Both the QLD guideline and the Chinese Consensus showed suboptimal performance in estimating VTE risk. Further research is urgently needed to develop more effective RAMs to aid in the prevention of postpartum VTE.